X‐Ray Writing of Metallic Conductivity and Oxygen Vacancies at Silicon/SrTiO3 Interfaces. (8th April 2019) - Chikina, Alla; Caputo, Marco; Naamneh, Muntaser; Christensen, Dennis Valbjørn; Schmitt, Thorsten; Radovic, Milan; Strocov, Vladimir N.
Abstract: Tunable electronic properties of transition metal oxides and their interfaces offer remarkable functionalities for future devices. The interest in these materials has been boosted with the discovery of a 2D electron gas (2DEG) at SrTiO3 (STO)‐based interfaces. For the majority of these systems, oxygen vacancies play a crucial role in the emergence of interface conductivity, ferromagnetism, and high electron mobility. Despite its great importance, controlling the density and spatial distribution of oxygen vacancies in a dynamic way remains extremely challenging. Here, lithography‐like writing of a metallic state at the interface between SrTiO3 and amorphous Si using X‐ray irradiation is reported. Using a combination of transport techniques and in operando photoemission spectroscopy, it is revealed in real time that the X‐ray radiation induces transfer of oxygen across the interface leading to the on‐demand formation of oxygen vacancies and a 2DEG in STO. The formed 2DEG stays stable in ambient conditions as the interface oxygen vacancies are stabilized by the capping of Si. The study provides a fundamental understanding of X‐ray‐induced redox reactions at the SrTiO3 ‐based interfaces and in addition shows the potential of X‐ray radiation for patterning stabile conductive pathways for future oxide‐based electronic devices. Abstract : The combination of transport techniques and in operando photoemission spectroscopy provides evidence of an redox reaction in the amorphous‐Si/SrTiO3 (STO) interface triggered via X‐ray. Transfer of oxygen across the interface leads to on‐demand formation of a metallic state. The coverage of STO by amorphous silicon preserves the metallic interface state and makes the heterostructure stable under ambient conditions.